Comparative floral morphology and anatomy of Thurniaceae, an early-diverging family in the cyperids (Poales, Monocotyledons) - Silva, Arthur de L. [UNESP]; Alves, Marccus V. S.; Coan, Alessandra [UNESP] (Springer, 2020)
Thurniaceae are positioned at the base of the cyperids, in Poales, as a sister group of Cyperaceae + Juncaceae. However, Rapateaceae + Mayacaceae have emerged related to these families in a recent phylogenetic study. Although Thurniaceae are morphologically similar to Juncaceae, studies are needed to evaluate characters with systematic value and that may help comprehend the reproductive biology in the family. In this regard, we investigate the floral morphology and anatomy of Prionium serratum and Thurnia sphaerocephala using standard techniques of scanning electron microscopy and light microscopy. The flowers of both species are trimerous, pentacyclic, with diplostemonous androecium and tricarpellate syncarpous gynoecium. Nevertheless, dimerous flowers with an inconsistent number of stamens also occur in T. sphaerocephala. Most floral traits of Thurniaceae are shared with Juncaceae and indicate putative plesiomorphies in the cyperids. However, no consistent data corroborates a link between Rapateaceae and Mayacaceae and the cyperids. The perigonium of Thurniaceae has diagnostic characters for the family, but also for each one of the species studied. The androecium is similar in P. serratum and T. sphaerocephala. In the gynoecium, the number of ovules, the length of the ovary zones, and the occurrence of ovary wall intrusions distinguish P. serratum from T. sphaerocephala and may have a correlation in the cyperids. Furthermore, the type of inflorescence, the color of flowers, and the type of stigma suggest that P. serratum is wind-pollinated and that T. sphaerocephala is insect-pollinated.
Keywords: Dimery; Floral biology; Floral structure; Gynoecium; Prionium; Thurnia